2014
DOI: 10.1007/s00775-014-1143-4
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibitory effects of the Diruthenium-Ibuprofen compound, [Ru2Cl(Ibp)4], in human glioma cells in vitro and in the rat C6 orthotopic glioma in vivo

Abstract: The Diruthenium-Ibuprofen compound [Ru2Cl(Ibp)4] (or RuIbp) is known to cause significant inhibition of C6 rat glioma cell proliferation in vitro. RuIbp increased the expression of cell cycle-related proteins such as p21 and p27 and the pro-apoptotic protein Bax, as well as causing a reduction in mitochondrial membrane potential and a modest increase in apoptosis in vitro. The present study extended these findings by (i) investigating the effects of RuIbp on human glioma cell line proliferation in vitro and (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…Ruthenium complexes have been published and identified in recent literature as anti-inflammatory and anti-cancer agents (1925). RuX as an anti-inflammatory agent may be due to the higher coordination numbers of transition metals (ruthenium and palladium), allowing transition metal complexes to have more diverse molecular geometry, unknown to organic molecules created by carbon (coordination number 4) (26).…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Ruthenium complexes have been published and identified in recent literature as anti-inflammatory and anti-cancer agents (1925). RuX as an anti-inflammatory agent may be due to the higher coordination numbers of transition metals (ruthenium and palladium), allowing transition metal complexes to have more diverse molecular geometry, unknown to organic molecules created by carbon (coordination number 4) (26).…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Previous studies based on circular dichroism (CD) and SDS-PAGE performed in our laboratory suggested that the RuIbp metallodrug binds to HSA and induces conformational changes in the protein secondary structure without causing significant protein cleavage [46]. The present work extends our studies by investigating the interactions of the Ru 2 (II,III) complexes, i.e., RuAc, RuIbp and RuKet, with HSA.…”
mentioning
confidence: 50%
“…More interestingly, Ru 2 -NSAID complexes are capable of inhibiting proliferation of glioma cancer cells. RuIbp was shown to exhibit anticancer activity in vitro (in rat and in human glioma cell lines) and also in vivo, thus revealing interesting properties for further studies targeting brain cancer therapy [47]. RuIbp and the analogue complex of Ketoprofen (HKet) ligand, [Ru 2 (Ket) 4 Cl] (or RuKet, figure 1c), display mild anti-proliferative activity in Caco-2 and HT-29 colorectal cancer cells [50].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Compound 1 has been used as a precursor to prepare a novel class of diruthenium(II,III) metallodrugs of the general formula [Ru 2 (RCOO) 4 Cl], where RCOO − is a carboxylate anion derived from a therapeutic drug 10c. In particular, metallodrugs containing carboxylate ligands derived from the nonsteroidal anti‐inflammatory drug ibuprofen10d,e or from γ‐linolenic acid10f,g were found to be active against glioma tumor models and have been investigated for partial elucidation of their mechanism of action. Moreover, the diruthenium–ibuprofenate complex shows anti‐inflammatory properties with reduced gastric ulceration in vivo compared to the ibuprofen parent drug 10h…”
mentioning
confidence: 99%